Conflict Management Styles and Staff Job Satisfaction in Nepalese Commercial Bank - Pathak, Nirdesh (Nepalese Journal of Economics, 2025)
This study examines the interplay between conflict management styles and staff job satisfaction in Nepalese commercial banks. Job satisfaction and job performance are the dependable variables. The independent variables are avoiding style, compromising style, accommodating style, dominating style, integrating style and collaborating style. The study is based on primary data with 128 observations. To achieve the purpose of the study, structured questionnaire is prepared. The correlation coefficients and regression models are estimated to test the significance and the conflict management styles and staff job satisfaction in Nepalese commercial bank. The study showed that avoiding style has a positive impact on job satisfaction and job performance. It indicates that increase in avoiding style leads to increase on job satisfaction and job performance. Likewise, compromising style has a positive impact on job satisfaction and job performance. It indicates that increase in compromising style leads to increase on job satisfaction and job performance. Similarly, accommodating style has a positive impact on job satisfaction and job performance. It means that accommodating style in the organization leads to increase on job satisfaction and job performance. Moreover, dominating style has a positive impact on job satisfaction and job performance. It indicates that better the dominating style, higher would be on job satisfaction and job performance. In addition, integrating style has a positive impact on job satisfaction and job performance. It reveals that higher the integrating style, higher would be the job satisfaction and job performance. Likewise, collaborating style has a positive impact on job satisfaction and job performance. It indicates that increase in collaborating style leads to increase on job satisfaction and job performance.